Internal fire probabilistic safety assessment preliminary work at research reactor triga puspati - Hashim, Zaredah; Kumar, Devintharaaj; Zakaria, Mohd Fazli; Hussain, Mohd Huzair; Mohd Sarif, Ahmad Hassan Sallehudin; Maskin, Mazleha
An internal fire analysis Level-I probabilistic safety assessment (PSA) for TRIGA PUSPATI (RTP) nuclear research reactor was initiated. Previous study on half-scope mode Level-I PSA, focusing only on internal initiating event, were developed for both full power and shutdown operational mode. Hence, in ensuring PSA remains relevant, a subsequent study to kept PSA up to date is a compulsory. The aim of this study is to present the step-by-step work done and the insights gained in identifying and screening significant compartments that are potential to had the worst consequences as an ignition sources. This preliminary study will only focus on RTP’s basement which consist of 3 compartments: switch room, battery room and basement hall. Procedure in data collection were based on IAEA document, Specific Safety Guide No. 3: Development and Application of Level 1 Probabilistic Safety Assessment for Nuclear Power Plants (SSG-3). Microsoft Excel was used as data collection media and internal fire hazard database development. A brief qualitative analysis using failure mode and effect analysis is also presented.